SISTEM INFORMASI PROFIL MAHASISWA PADA PENILAIAN PENGUJI PESSTA+ DI PERGURUAN TINGGI - Hani Dewi Ariessanti; Aris Martono; Danang Suprayogi (UNIVERSITAS RAHARJA, 2019)
Submission of information is an important thing in a system. A good system that is able to communicate to its users by conveying information correctly and clearly. In the examiner rating system found in Raharja College before the system still did not provide information about theprofile of the Thesis and Final Project students. Submitting the lack of information is felt to make the previously running system unable to communicate to its users. Therefore it is necessary to develop a student profile information system so that it can communicate to its usersclearly. After the examiner assessment system that has been developed becomes online, the student profile information system is also developed online by adding some information that can make the system more communicating to its users. Research to develop a student profile information system on the assessment of trial examiners using observational research methods, interviews and literature studies. The researcher made observations by looking at the shortcomings of the system, then conducting interviews with stakeholders, then the researchers sought similar research in order to solve the problems that had been obtained. It is expected that after being applied to the Testing Assessment system, the delivery of information regarding the profile of the Thesis trial and Final Project students can be better and clearer. Because information about student profiles is very important for examiners in providing trial scores to Thesis and Final Project students.